Retention of fiber posts in different dentin regions: An in vitro study - Padmanabh Jha; Mesha Jha (Wolters Kluwer Medknow Publications, 2012)
Aim: The aim of this study was to evaluate the influence of different regions of dentin within the post space on the retention of fiber posts. Materials and Methods: Ten human incisors with straight roots were selected for this study. Endodontic treatment of the specimens was done. The post spaces were created immediately after obturation and the posts were luted with dual-cure resin cement. Approximately 2.5-mm-thick sections were made from the coronal, middle, and apical thirds of the post space and thus we had three groups: Group I: Cervical, Group II: Middle, Group III: Apical. The specimens were tested on a universal testing machine. Statistical analysis was done using the unpaired Student's t-test and one-way ANOVA test. Result: The best push-out strength was obtained with the apical sections (14.69±0.298 MPa), followed by the middle (10.66±0.34 MPa) and cervical sections (9.73±0.42 MPa). Conclusion: highest pust out strengths were obtained in apical sections followed by middle and coronal.